Assessing the Role of International Judicial Advisory Opinions in the Evolution of International Environmental Law in Response to Climate Change - Phuong Dung Nguyen; Yen Thi Hong Nguyen (University of Bologna Law Review)
Climate change has emerged as a global menace, threatening human existence and Earth’s biodiversity. The urgency to address this crisis intensifies, yet the window for effective action is narrowing. Failure to act disproportionately impacts marginalised communities, highlighting the need for legal clarity. Judicial authorities, such as the International Court of Justice (I.C.J.), the International Tribunal for the Law of the Sea (I.T.L.O.S.), and the Inter-American Court of Human Rights (I.A.C.H.R.), have increasingly been requested to provide advisory opinions on addressing climate change. Although generally non-binding, these advisory opinions have become a vital source of international law, particularly in the evolving fields of environmental and human rights law, and can, in certain institutional and legal framework contexts, carry significant legal and practical influence. They offer the flexibility needed to develop new instruments or legal and policy reform in response to changing practices. This article explores the evolution of advisory opinions, their contributions to addressing climate change, and the benefits and challenges of utilizing them to mitigate climate change. It also attempts to delineate reflections and implications concerning the development of advisory opinions in the context of climate change.